Theory and New Applications of Ex Situ Lift Out. (16th July 2015) - Giannuzzi, Lucille A.; Yu, Zhiyang; Yin, Denise; Harmer, Martin P.; Xu, Qiang; Smith, Noel S.; Chan, Lisa; Hiller, Jon; Hess, Dustin; Clark, Trevor
Abstract: The ex situ lift out (EXLO) adhesion forces are reviewed and new applications of EXLO for focused ion beam (FIB)-prepared specimens are described. EXLO is used to manipulate electron transparent specimens on microelectromechanical systems carrier devices designed for in situ electron microscope analysis. A new patented grid design without a support film is described for EXLO. This new slotted grid design provides a surface for holding the specimen in place and also allows for post lift out processing. Specimens may be easily manipulated into a backside orientation to reduce FIB curtaining artifacts with this slotted grid. Large EXLO specimens can be manipulated from Xe + plasma FIB prepared specimens. Finally, applications of EXLO and manipulation of FIB specimens using a vacuum probe lift out method are shown. The vacuum probe provides more control for placing specimens on the new slotted grids and also allows for easy manipulation into a backside configuration.